Restoration of motor learning in a mouse model of Rett syndrome following long-term treatment with a novel small-molecule activator of TrkB - Ian Adams; Tao Yang; Frank M. Longo; David M. Katz (The Company of Biologists, 2020)
Reduced expression of brain-derived neurotrophic factor (BDNF) and impaired activation of the BDNF receptor, tropomyosin receptor kinase B (TrkB; also known as Ntrk2), are thought to contribute significantly to the pathophysiology of Rett syndrome (RTT), a severe neurodevelopmental disorder caused by loss-of-function mutations in the X-linked gene encoding methyl-CpG-binding protein 2 (MeCP2). Previous studies from this and other laboratories have shown that enhancing BDNF expression and/or TrkB activation in Mecp2-deficient mouse models of RTT can ameliorate or reverse abnormal neurological phenotypes that mimic human RTT symptoms. The present study reports on the preclinical efficacy of a novel, small-molecule, non-peptide TrkB partial agonist, PTX-BD4-3, in heterozygous female Mecp2 mutant mice, a well-established RTT model that recapitulates the genetic mosaicism of the human disease. PTX-BD4-3 exhibited specificity for TrkB in cell-based assays of neurotrophin receptor activation and neuronal cell survival and in in vitro receptor binding assays. PTX-BD4-3 also activated TrkB following systemic administration to wild-type and Mecp2 mutant mice and was rapidly cleared from the brain and plasma with a half-life of ∼2 h. Chronic intermittent treatment of Mecp2 mutants with a low dose of PTX-BD4-3 (5 mg/kg, intraperitoneally, once every 3 days for 8 weeks) reversed deficits in two core RTT symptom domains - respiration and motor control - and symptom rescue was maintained for at least 24 h after the last dose. Together, these data indicate that significant clinically relevant benefit can be achieved in a mouse model of RTT with a chronic intermittent, low-dose treatment paradigm targeting the neurotrophin receptor TrkB.